Effect of kinesio taping versus mulligan Taping in treatment of heel pain - Dr. SHEFALI MEHTA,; Dr.SOUMIK BASU,; Prof. TUSHAR J.PALEKAR,; Dr. NILAM DAVE, (International Journal of Pharma and Bio Sciences, 2017)
Plantar fasciitis is a common chronic overuse injury of the plantar fascia with its painful inï¬‚ammation. The exact aetiology of plantar fasciitis is unclear being multi-factorial .30 subjects fulfilling inclusion criteria were randomly allotted into two groups by randomized control trial. Initial intensity of pain was measured using visual analogue scale, disability measured by foot functional index. Both groups received 2 sessions of kinesio and mulligan taping on every 3rd day respectively. Along with taping the patient followed the conventional physiotherapy protocol for plantar fasciitis. Patients were reassessed after 6 days of treatment. This study demonstrates that both the techniques are effective in relieving pain. However; Mulligan Taping Technique showed better results to alleviate pain and improve functional measures (p value for VAS <0.012 and FFI <0.001). The tape is applied in such a way that therapeutic glide is maintained presumably taking off the force from plantar fascia and hence reducing pain.